Child protection recipe: parenting guideline to prevent children from cybersex addiction / Wan Saidatul Nasuha Wan Maizon, Siti Nur Fathanah Abd Hamid and Yarina Ahmad - Wan Maizon, Wan Saidatul Nasuha; Abd Hamid, Siti Nur Fathanah; Ahmad, Yarina (2021)
As many as 3,980 children between the ages of 10 to 19 years old were pregnant out of wedlock in 2018 and every year up to 100 babies are dumped in Malaysia, where a majority of them were dead when found. Based on previous research undertaken surrounding this issue, it shows that one of the main factors is due to imitation of pornographic material by the children (Bahori & Ismail, 2018). The statistic shows the seriousness of cybersex addiction as a growing phenomenon which brings about significant impact to children. Moreover, if this issue fails to be prevented by the relevant parties such as parents, guardians, society, and government agencies, it will result in detrimental effects on children and the country, since children are the future generation and talents in the country. Thus, their healthy growth and development should be prioritised. Due to this gap, this paper aims to present an innovative idea which is known as 'Child protection recipe: Parenting guidelines to prevent children from cybersex addiction'. Through a review of the parenting guidelines, this paper has found that if parents abide by these guidelines provided in the book, parents can prevent their children from succumbing to cybersex addiction effectively. Hence, parents require a proper parenting guideline to provide proper supervision and monitoring mechanisms for their children.